2023
DOI: 10.1007/s42773-023-00224-y
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the effect and mechanism of FeN3-doped biochar for greenhouse gas mitigation

Abstract: Paddy fields are a major emission source of greenhouse gases (GHGs) [for instance, methane (CH4), nitrous oxide (N2O), and carbon dioxide (CO2)] among agricultural fields. Biochar has been deemed a potential candidate for the reduction of GHGs in paddy fields. However, there is no consistent conclusion that biochar can simultaneously reduce emissions of CH4, N2O, and CO2. Herein, we proposed the FeN3-doped biochar (FG) as an excellent material for GHGs restriction in paddy fields via the first-principles calcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The FeN3-doped biochar demonstrated adequate adsorption capabilities for several GHGs in paddy fields (CH4, CO2, and N2O) compared to pure biochar. This enhanced the adsorption energies to -1.37, -1.54, and -2.91 eV, respectively, and altered GHG molecule structure [19]. Additionally, the density of state and partial density of state analyses showed that the occurrence of a significant electron energy up-or downshift of the electron for Fe d, C p, O p, or N p orbitals when CH4, CO2, or N2O is adsorbed is what causes FeN3-doped biochar to demonstrate exceptional adsorption capacity.…”
Section: Carbon Sequestration and Utilization In Agriculturementioning
confidence: 99%
See 1 more Smart Citation
“…The FeN3-doped biochar demonstrated adequate adsorption capabilities for several GHGs in paddy fields (CH4, CO2, and N2O) compared to pure biochar. This enhanced the adsorption energies to -1.37, -1.54, and -2.91 eV, respectively, and altered GHG molecule structure [19]. Additionally, the density of state and partial density of state analyses showed that the occurrence of a significant electron energy up-or downshift of the electron for Fe d, C p, O p, or N p orbitals when CH4, CO2, or N2O is adsorbed is what causes FeN3-doped biochar to demonstrate exceptional adsorption capacity.…”
Section: Carbon Sequestration and Utilization In Agriculturementioning
confidence: 99%
“…Crop residues 33% soil CO2, 23% soil N2O [5] Potassium doped Over 2.6 Gt CO2-C(eq) per year [14] Corn residues Carbon sequestration increased by 16%, 132% CH4 [15] Maize straw/Pyrolysis and aging Significant reduction of CO2 [16] FeN3-doped Great absorption of CH4, CO2, or N2O [19] , 03011 (2023) ICREE 2023 https://doi.org/10.1051/e3sconf/202342403011 424 E3S Web of Conferences Following the addition of biochar to the soil, there were changes in GHG emissions, including enhanced plant growth (which stores more carbon in vegetation), decreased non-CO2 GHG emissions from the soil, and decreased mineralization of soil organic matter (Table 1).…”
Section: Feedstock/ Modification Reduction Of Ghg Emission Referencementioning
confidence: 99%